EXPERIENCES OF NURSES DURING THE CORONAVIRUS PANDEMIC AND EFFECT OF NEURO-LINGUISTIC PROGRAMMING ON NURSES' GREATEST FEARS: A QUALITATIVE STUDY - DOĞAN, Aysel; KARASU, Fatma; BİRİMOĞLU OKUYAN, Canan (Göbeklitepe Medical Science Journal, 2021)
Purpose: This study was performed to investigate nurses' experiences during the coronavirus pandemic and the effect of neuro-linguistic programming on nurses' greatest fears. Methods: Phenomenological research design was used to guide data collection and analysis. Ethical procedures were taken into account, and 11 nurses who provided one-on-one care and treatment to COVID-19 patients through semi-structured interviews were included in the study. Results: Most of the nurses stated that their fears and worries are mostly due to the fear of infecting their families and death. In this process, the greatest fear experienced by nurses was reduced with NLP.